Improvement of Growth, Yield and Quality of Tomato (Solanum lycopersicum L.) cv. Azad T-6 with Foliar Application of Zinc and Boron - Meena, D. C.; Maji, S.; Meena, J. K.; Kumawat, R.; Meena, K. R.; Kumar, S.; Sodh, K. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted to find out the response of zinc and boron on improvement of growth, yield and quality of tomato (Solanum lycopersicum L.) cv. Azad T-6. The experiment was layout in Randomized Block Design with three replication and 12 treatments. Treatment combinations are T0-Control (water spray), T1-Zinc (50 ppm), T2-Zinc (100 ppm), T3-Zinc (150 ppm), T4-Boron (50 ppm), T5-Boron (100 ppm), T6-Boron (150 ppm), T7-Zinc (50 ppm)+Boron (50 ppm), T8-Zinc (100 ppm)+Boron (100 ppm), T9-Zinc (150 ppm)+Boron (150 ppm), T10-Zinc (100ppm)+Boron (50 ppm), T11-Zinc (150 ppm)+Boron (50 ppm). It was found that the vegetative growth in terms of plant height and number of branches at various stages (30, 60 and 90 Days after transplanting) was greatly influenced by the application of micronutrients Zn and B. Among them treatment T5-Boron (100 ppm) significantly increased the plant height (61.23 cm at 90 DAT) and number of branches (16.17 plant-1 at 90 DAT) compared to others. Whereas, application of zinc and boron each at 100 ppm (T8) caused early flowering (31.95 DAT) as well as showed maximum number of flowers (75.21) and fruit yield (93.10 t ha-1). It was also revealed that the treatment T8 improved the physico-chemical qualities of tomato fruits specially improved the TSS:acid ratio (10.98). Thus, the study indicated that application of boron and zinc either solely or in combination is quite beneficial for vegetative growth, flowering and fruiting as well as quality improvement of tomato fruits (Azad T-6) grown under high pH soil (pH 8.2) of Lucknow.